(untitled) (Revista de Ciências Agroveterinárias, 2005)
The Marssonina Blotch, caused by the fungus Marssonina mali (Henn.), was observed on the cv Eva, causing intense defoliation during the 2001/2002 and 2002/2003 growing seasons. This is the first report of the disease on this cultivar in the Central Basin of Rio Grande do Sul State. The objective of this study was to identify the fungi and quantify the intensity of disease in apples cv. Eva of the Agronomic Experimental Station orchard of the UFRGS. The material for analysis was obtained from acervuli that exist in the lesions, through the scratching of the vegetable tissue, and its observation in the optical microscope. The incidence of the disease was evaluated by the percentage of attacked leaves. Its severity was quantified using a scale of notes that considers the foliate area with lesion. The results indicate the need to control this disease on the Eva cultivar.